2023
DOI: 10.1186/s40246-023-00519-y
|View full text |Cite
|
Sign up to set email alerts
|

Total RNA sequencing reveals gene expression and microbial alterations shared by oral pre-malignant lesions and cancer

Abstract: Head and neck cancers are a complex malignancy comprising multiple anatomical sites, with cancer of the oral cavity ranking among the deadliest and the most disfiguring cancers globally. Oral cancer (OC) constitutes a subset of head and neck cancer cases, presenting primarily as tobacco- and alcohol-associated oral squamous cell carcinoma (OSCC), with a 5-year survival rate of ~ 65%, partly due to the lack of early detection and effective treatments. OSCC arises from premalignant lesions (PMLs) in the oral cav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In fact, evidence indicates that both P. gingivalis and F. nucleatum are endowed with tumorigenic activities which are likely to favor OSCC onset and/or progression [5]. Confirming this, the dysplastic and/or hyperplastic lesions that often precede OSCC development (oral pre-malignant diseases, OPMDs) [8] are densely populated by pathogenic bacteria, including F. nucleatum or P. gingivalis, and display a reduced number of saprophytic bacteria as compared with healthy oral mucosa [9,10]. In OSCCs, the presence of F. nucleatum and P. gingivalis becomes even more evident, and its intensity parallels the clinical progression of the disease, positively correlating with the tumor size and lymph node metastases [9,10].…”
Section: Introductionmentioning
confidence: 91%
“…In fact, evidence indicates that both P. gingivalis and F. nucleatum are endowed with tumorigenic activities which are likely to favor OSCC onset and/or progression [5]. Confirming this, the dysplastic and/or hyperplastic lesions that often precede OSCC development (oral pre-malignant diseases, OPMDs) [8] are densely populated by pathogenic bacteria, including F. nucleatum or P. gingivalis, and display a reduced number of saprophytic bacteria as compared with healthy oral mucosa [9,10]. In OSCCs, the presence of F. nucleatum and P. gingivalis becomes even more evident, and its intensity parallels the clinical progression of the disease, positively correlating with the tumor size and lymph node metastases [9,10].…”
Section: Introductionmentioning
confidence: 91%
“…These conditions include whitish (leukoplakia) and red patches (erythroplasia, erythroplakia), lichen planus and rhomboid tongue inflammation. Conditions directly leading to the development of malignancy include small-, mediumand high-grade squamous metaplasia or dysplasia and carcinoma in situ [27,[29][30]. SCC accounts for more than 90% of all OCs [31][32].…”
Section: Histologymentioning
confidence: 99%
“…A meta-analysis found that HPV 16/18 was strongly associated with OLP and OLK [21]. In general, continuous microbial changes are observed throughout the development of OSCC [22]. However, further research is required to elucidate the relationship between microbes and the risk of malignant transformation [23].…”
Section: Oral Microbiota Participating In the Occurrence Development ...mentioning
confidence: 99%